Coptic Orthodox Christianity: religious transformation in the time of Neoliberalism - Kalliney, Marsil (AUC Knowledge Fountain, 2010)
While the Coptic Orthodox Church celebrates a unique historical trajectory, contemporary Copts' conceptualization of religious discourses reflects a transformation impacted by political and economic global forces. The international prevailing ideological paradigm of neoliberalism is highlighted by the shift from governments into individuals through economic and political practices. This thesis illustrates the transformation using an example of a Coptic charity organization redefining itself to be a non-governmental organization (NGO) in response to the dominant paradigm of neoliberalism. The organization is a microcosm reflecting global financial and political forces as well as members' religious beliefs as they relate to these global forces. This project highlights the narratives of the members of the organization and the church clergy.